1997
DOI: 10.1038/sj.dmfr.4600214
|View full text |Cite
|
Sign up to set email alerts
|

Bifid mandibular condyle.

Abstract: The bifid mandibular condyle remains a relatively uncommon entity although the number of reports continues to accumulate, usually as incidental radiographic findings. It would appear that it may arise in at least two different ways, traumatically and developmentally. A case is presented of a unilateral bifid condyle in a young female. From the radiological examination, including CT, the left condyle was seen to be divided medio-laterally by a groove located on the anterior aspect. A history of trauma was incon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
0
15
0
2
Order By: Relevance
“…A common belief is that trauma plays a role in aetiology in 11–25% of cases (2, 7–11, 17). It has also been reported that bifid condyle formation could result from healing and remodelling after trauma and fractures of condylar region and condylectomy during infancy and puberty (6, 8–11, 18, 19). However, in the majority of the published cases, there is no sign of any etiological agent (2, 4, 5, 12, 20).…”
Section: Discussionmentioning
confidence: 99%
“…A common belief is that trauma plays a role in aetiology in 11–25% of cases (2, 7–11, 17). It has also been reported that bifid condyle formation could result from healing and remodelling after trauma and fractures of condylar region and condylectomy during infancy and puberty (6, 8–11, 18, 19). However, in the majority of the published cases, there is no sign of any etiological agent (2, 4, 5, 12, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of one or more such septae, or possible rupture of some of the blood vessels, might affect ossification and yield a bifid condyle. 6,13 In 1972, Poswillo 14 performed a condylectomy in four adult monkeys (Macaca irus), while keeping the joint disk intact. A bifid condyle formed in one of the cases.…”
Section: Figurementioning
confidence: 99%
“…The healing and remodeling process after condylar fracture has also been proposed as a possible pathogenic mechanism for bifid condyle. 3,13 Loh and Yeo 7 classified the bifid condyles found in humans according to antecedents of trauma. They found that most patients with this morphological anomaly had suffered no past traumas.…”
Section: Figurementioning
confidence: 99%
“…It is reported to affect only one condyle, and the observation of bilateral BMC is exceptionally rare. Often, BMC is usually identified as an incidental finding on routine radiographic examination [3]. This paper reports a series of clinical cases of BMC possibly resulting from trauma, with emphasis on clinical diagnosis, radiographic and tomographic features, and management.…”
Section: Introductionmentioning
confidence: 99%